Specific Activity of Lactate Dehydrogenase in Muscle and Liver Tissues of Rats Exposed to Intermittent Hypobaric Hypoxia - Syarifah Dewi; Adiba Nur Ashri Ramadhani; Khoiriyyah Amalia Az-zahra; Wardaya Wardaya (BIO Integration)
As the altitude increases, the partial pressure of oxygen will decrease and cause hypobaric hypoxia conditions. During hypoxia, the anaerobic glycolysis will be activated, which is facilitated by the lactate dehydrogenase (LDH) enzyme. This study aimed to analyze the LDH-specific activity in rat muscle and liver tissue, as well as lactate and glucose levels in blood plasma after intermittent hypobaric hypoxia exposure. Twenty-five Wistar rats were divided into five groups: one control group and four hypobaric hypoxia (HH) exposure groups consisting of group 1 (1× HH), group 2 (2× HH), group 3 (3× HH), and group 4 (4× HH) with a range of 7 days between exposure. This study found that LDH-specific activity increased in muscle tissues in group 1, but then decreased in the intermittent group (groups 2–4). The change in LDH-specific activity in muscle tissues was similar to the change in lactate plasma levels. Interestingly, in liver tissues, there was a slight increase in the LDH-specific activity in group 1, and it started to increase significantly in group 2 and kept increasing in groups 3 and 4. The change in LDH-specific activity in liver tissues was similar to the change in glucose plasma level. We conclude that the LDH activity in muscle tissue contributes to lactate plasma levels, but the LDH activity in liver tissue contributes to maintaining glucose plasma after intermittent hypobaric hypoxia exposures. This finding could be implemented in individuals who experience intermittent hypoxia exposures or in various diseases with hypoxic conditions as their pathogenesis.